2007
DOI: 10.1016/j.neuroimage.2007.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and BOLD responses to a memory encoding task: A comparison between healthy young and elderly adults

Abstract: Functional magnetic resonance imaging (fMRI) studies of the medial temporal lobe have primarily made use of the blood oxygenation level dependent (BOLD) response to neural activity. The interpretation of the BOLD signal as a measure of medial temporal lobe function can be complicated, however, by changes in the cerebrovascular system that can occur with both normal aging and age-related diseases, such as Alzheimer's disease. Quantitative measures of the functional cerebral blood flow (CBF) response offer a use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 74 publications
5
97
1
1
Order By: Relevance
“…However, it should be noted that greater percent change CBF during novel relative to familiar image presentation could reflect a lower level of absolute CBF response during the familiar image condition. As our recent work (Restom et al, 2007) suggests, the greater percent change CBF response during novel picture encoding in the older participants may reflect a lower level of CBF response during the familiar image condition, which would be consistent with the observed age-related reduction in resting-state CBF.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, it should be noted that greater percent change CBF during novel relative to familiar image presentation could reflect a lower level of absolute CBF response during the familiar image condition. As our recent work (Restom et al, 2007) suggests, the greater percent change CBF response during novel picture encoding in the older participants may reflect a lower level of CBF response during the familiar image condition, which would be consistent with the observed age-related reduction in resting-state CBF.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, ASL has important implications for diagnosis, treatment monitoring, and outcome prediction in dementia, stroke, and other neurological diseases (Warach et al, 1996). Initial studies assessing both BOLD and CBF in the MTL during encoding have demonstrated the feasibility of this technique in older adults (Restom et al, 2007). The main challenge is the relatively low contrast-to-noise ratio of the CBF measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age is associated with changes in CBF (Biagi et al, 2007;Parkes et al, 2004), which have been shown to influence BOLD fMRI results (Restom et al, 2007). In particular, age-related increases in the BOLD signal may be partly explained by regional reductions in CBF.…”
Section: Perfusion Mrimentioning
confidence: 99%
“…While differences in the experimental design, types of stimuli, and contrasts of interest might explain, to some extent, the discrepant results across studies, biological and technical factors also need to be taken into account, such as age-related changes in cerebral blood flow (CBF; Biagi et al, 2007;Parkes et al, 2004;Restom et al, 2007). Furthermore, the complex anatomy of regions such as the MTL has been shown to be poorly registered to a brain template using standard spatial normalization procedures (Kirwan et al, 2006;Salmond et al, 2002).…”
Section: Introductionmentioning
confidence: 99%